Boundaries of Legitimate Debate: right-wing Extremism in Norwegian News Media in the Decade after the July 22, 2011 Attacks - Larsen, Anna Grøndahl (Perspectives on terrorism, 2021)
How to deal with voices deemed deviant and extremist is a recurring topic of debate, including questions such as whether deviant actors and ideas should be silenced or included in public debates. As with terrorist attacks in other parts of the world, the attacks in Norway on July 22, 2011 ignited discussions on the limits of legitimate debate, including the role of mainstream politicians and news media in setting the boundaries for what is appropriate in public debates. This article explores news debates on right-wing extremism in the decade after the attack, shedding light on how boundaries between legitimacy and deviance were drawn and negotiated. Analyzing articles on right-wing extremism in two national news outlets in Norway (NRK and VG) between 2013 and 2019, the author explores who got to speak and define the debate, to what extent actors deemed extremist were granted a voice, and how boundaries between legitimate and illegitimate political actors were negotiated. First, the analyses show that although the coverage was dominated by elites, actors deemed extremist were relatively prominent sources. Second, political and cultural elites engaged in continuous negotiations over the boundaries of legitimate and appropriate debate. However, third and relatedly, the analysis illustrates that debates concerning possible links between the views of legitimate elite actors—such as politicians in parliament—and deviant extremists were challenging to initiate.